2021
DOI: 10.1111/mpp.13042
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodesmata play pivotal role in sucrose supply to Meloidogyne graminicola‐caused giant cells in rice

Abstract: Plant-parasitic nematodes are soilborne pathogens of crops that cause tremendous yield losses (Jones et al., 2013). Sedentary plant-parasitic nematodes invade plant roots and establish feeding sites in the root tissue, which are unique organs in plant roots, characterized by a higher metabolic activity and different cell wall composition compared to normal root cells (Kyndt et al., 2013; Zhang

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Sugar transporter genes AtSUC2 and gall specific promoter TobRB7 , have been identified to be involved in the feeding site of nematodes ( Opperman et al., 1994 ; Juergensen et al., 2003 ). Recently, sucrose transport was found to be mostly dependent on plasmodesmata-mediated sucrose supply from the rice root phloem to M. graminicola -caused giant cells, and OsSWEET11 to 15 and OsSUTs play no major role in this process ( Xu et al., 2021 ). In our experimental results, GUS activity in the AtSWEET1 reporter was not observed in non-galls of the root, which is consistent with Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar transporter genes AtSUC2 and gall specific promoter TobRB7 , have been identified to be involved in the feeding site of nematodes ( Opperman et al., 1994 ; Juergensen et al., 2003 ). Recently, sucrose transport was found to be mostly dependent on plasmodesmata-mediated sucrose supply from the rice root phloem to M. graminicola -caused giant cells, and OsSWEET11 to 15 and OsSUTs play no major role in this process ( Xu et al., 2021 ). In our experimental results, GUS activity in the AtSWEET1 reporter was not observed in non-galls of the root, which is consistent with Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different architectures among the three types of M. graminicola -caused NFSs might lead to a different parasitism ability of M. graminicola on rice. Noteworthy, the type I of M. graminicola -caused NFSs on rice that shows a similar size for its lateral and longitudinal areas presents a relatively larger surface than both types II and III, which could facilitate material and signal exchange between GCs and their neighboring cells (Bartlem et al 2014 ; Kyndt et al 2016 ; Xu et al 2021 ). This might explain why type I is the dominant architectural type of NFSs in rice galls caused by M. graminicola and type II at later parasitic J2 stage transforms into type I at J3 stage.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all SUT genes except for OsSUT2 show very weak expressions in the root at the transcriptional level. Xu et al [ 53 ] reported that none of the rice SUT genes were expressed in the root, as detected via GUS expression. However, another investigation employing the same method showed that OsSUT1 was expressed in the root of rice shortly after seed germination [ 34 ].…”
Section: Physiological Functions Of Rice Sut Sucrose Transportersmentioning
confidence: 99%